Gender differences in spatial awareness in immersive virtual environments: a preliminary investigation - Paraskeva, Christos; Koulieris, George Alex; Coxon, Matthew; Mania, Katerina (Association for Computing Machinery (ACM), 2012)
This paper presents an experiment exploring gender differences in spatial navigation, memory performance and spatial awareness through a complex Virtual Environment (VE). The immersive simulation consisted of a radiosity-rendered space divided in four zones including a kitchen area, a dining area, an office area and a lounge area. The space was populated with objects consistent as well as inconsistent with each zone's context. The simulation was then displayed on a stereo head tracked Head Mounted Display. Participants were separated in two groups based on their gender. After being exposed to the VE, they completed an object-based memory recognition task. Participants also reported one of two states of awareness following each recognition response which reflected either the recollection of contextual detail or informed guesses. It was found that reported awareness states interacted with the context consistency of the objects: participants recollected more contextual detail when correctly identifying inconsistent objects compared to consistent objects. Furthermore, a clear gender difference was found with female participants correctly identifying objects in their correct location more often than the male participants.
EPrint Processing Status: Full text deposited in DRO